2017
DOI: 10.1016/j.theriogenology.2016.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Sperm morphometry and chromatin condensation in Nelore bulls of different ages and their effects on IVF

Abstract: The aim of this study was to evaluate the chromatin packing and sperm head morphometry of cryopreserved semen of Nelore bulls (Bos taurus indicus) of different ages. Furthermore, the influence of the degree of chromatin compaction on in vitro embryo production (IVP) was investigated. Forty bulls were divided into three groups: young (1.8-2 years), adult (3.5-7 years), and senile (8-14.3 years). The ejaculates were frozen according to standards established by the Artificial Insemination Center located in the So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 38 publications
3
27
0
1
Order By: Relevance
“…The rationale behind these investigations was that if abnormal head morphology was a characteristic of young bull spermatozoa this might be due to nuclear alterations as it is supported by several studies [3134]. To our knowledge there is no other study that has focused on the bull sperm nuclear integrity upon aging.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The rationale behind these investigations was that if abnormal head morphology was a characteristic of young bull spermatozoa this might be due to nuclear alterations as it is supported by several studies [3134]. To our knowledge there is no other study that has focused on the bull sperm nuclear integrity upon aging.…”
Section: Discussionmentioning
confidence: 98%
“…These points are rather important in the bovine industry for the efficiency and the cost effectiveness of insemination programs. Regarding bovine sperm nuclear condensation, Kipper et al (2017) [34] noted that spermatozoa from young bulls were morphometrically larger compared to those from older bulls and that alterations in chromatin condensation were related to heads with greater diameters. In another study concerning a different model of agricultural interest, Martí et al (2011) [35] morphometrically evaluated the heads of sperm cells from young goats shortly after reaching sexual maturity and observed heads with larger sizes compared to those of the adult animals, indicating a possible transition period between puberty and full sperm head size maturity.…”
Section: Discussionmentioning
confidence: 99%
“…The description of ellipticity, elongation, rugosity and regularity parameters is fundamental for distinguishing normal‐format gametes from amorphous, round and/or very sharp shaped heads (Bergstein et al, ). The association of these data with area and perimeter values can be used to optimize seminal analysis in automated systems, as well as they subsidize the creation of clustering software that provides information about genetic characteristics, such as chromatin stability (Kipper et al, ); differentiation of sperm X and Y (Santolaria et al, ); fertility potential (Ramón, Soler, et al, ); and resistance to cryogenic process (Núñez‐Martínez, Moran, & Peña, ; Ramón, Pérez‐Guzmán, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The description of ellipticity, elongation, rugosity and regularity parameters is fundamental for distinguishing normal-format gametes from amorphous, round and/or very sharp shaped heads (Bergstein et al, 2014). The association of these data with area and perimeter values can be used to optimize seminal analysis in automated systems, as well as they subsidize the creation of clustering software that provides information about genetic characteristics, such as chromatin stability (Kipper et al, 2017); differentiation of sperm X and Y (Santolaria et al, 2016); fertility potential (Ramón, Soler, et al, 2013); and resistance to cryogenic process ( Thus, the sperm morphologically normal of the cat can be described as an ovoid-shaped cell, being relatively longer than wide, since the ellipticity was >1 and the elongation was 21.3 ± 0.12. The rugosity value (0.14 ± 0.00) categorized a greater heterogenicity in the size of the feline sperm, since it was less than 1 and closer to 0, different from that observed in the bovine species (0.74 ± 0.001) (Santolaria et al, 2016) and caprine (0.79 ± 0.01) (Aragão et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the detection of spermatozoa with a lack of protamines is indicative of bull AI subfertility. The research regarding Nelore cattle showed that the spermatozoa from young bulls had larger head diameters due to the lower protamination level and resultant deficiency of chromatin condensation, compared with the spermatozoa from adult bulls 72. This might account for the cause of unstable results of AI when using cryopreserved spermatozoa from young bulls.…”
Section: Nuclear Proteinsmentioning
confidence: 99%